Exploring on factors that influence mothers to choose epidural analgesia during the labor process - Rahmat, Rozanna; Puteh, Syabina; Sa'at, Siti Fatimah; Mamat, Rohani; Musa, Mazlinda; Sidek Ahmad, Zulkhairul Naim (Universiti Putra Malaysia, 2025)
Introduction: This study aims to identify factors influencing pregnant women in choosing epidural analgesia during labor. Statistics from Raja Permaisuri Bainun Hospital (HRPB), Ipoh, revealed a rise in epidural usage from 2019 to 2021, indicating a growing demand and underlying factors for it. Purpose: To determine demographic characteris- tics and external factors influencing mothers’ choice of epidural analgesia during labor. Methodology: This quanti- tative, descriptive cross-sectional study involved 30 respondents, calculated using Epical 2000 software for a 95% confidence interval. Inclusion criteria encompassed primigravida or multigravida mothers with spontaneous vaginal delivery. A questionnaire was adapted from Harkins et al. (2006) which consists of 10 questions for part A and 15 questions for part B to gather research data. Result: The largest group was aged 23-27 years (33.3%), followed by 28- 32 years (26.7%), 33-37 years (20.0%), 38-42 years (13.3%), and 18-22 years (6.7%). The mean age was 29.63 years with a standard deviation of 5.568 years, indicating a predominantly young population with some age variability. Most of the respondents’ information came from medical experts, and the main motivation for selecting an epidural was to reduce and control labor discomfort. Conclusion: This study provides essential baseline data for health educa- tion on pain management during labor. It enhances nurses’ understanding of factors influencing women’s preference for epidural analgesia, facilitating improved patient care.